THE COMPLEXITY IN COPING CONFLICTING GROUPS IN SURROUNDING NUSAKAMBANGAN ISLANDS CENTRAL JAVA INDONESIA - Khairu Roojiqien Sobandi (Diponegoro University, 2011)
This study explores social and political conflicts in grassroots level, specifically, the challenge of natural degradations on a mangrove-fringed lagoon in Central Java, Indonesia. Segara Anakan is a significant environmental zone, with many unique ecosystem features, all of which are under threat from illegal land reclamation and timber theft, which have caused great damage. This study analyses how conflict arises between groups and how the rulers interact with villagers in Kampung Laut sur-rounding Nusakambangan Island. The result shows, as Reichel et al. (2009) notes, population growth and lagoon sedimentation indeed have directing to crucial conflicts between groups. However, histori-cal and the rulers approach factors also contribute to Kampung Laut conflicts. Long historical journey contribute to the formation of Kampung Laut villagers’ characters. It is the history of Galuh and Mata-ram Kingdoms’ networks through Babad Pasirluhur and Tanah Jawi in conquering Nusakambangan. More importantly, rulers’ policies and state apparatuses approaches also contribute to the creation of Kampung Laut villagers’ identity. The policies are often inconsistent and create more problems than solutions. Thus, dissatisfaction has directing to the creation of Kampung Laut identity marker as rebel-lions. In short, this hard situation led to conflicts between villagers and rulers. Our study suggest that it is very important to bring the state back in on the isolated and poor area like Kampung Laut Sub-District through more affirmative regional public policies and more over create additional income re-sources, for example eco-tourism that could support its sustainable outcomes.